The Representation of Morality and Its Consequences in Shakespeare’s Timon of Athens - Mhd Agri Amri; Melyana Pinem; Naomi Pricilia Tarigan; Endelina Miranda Marpaung; Syamsul Bahri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Literary works are not only created for entertainment, but also to describe human life, which is full of values and moral issues. William Shakespeare's play ‘Timon of Athens’, which shows how a person is tested when betrayed by wealth, power, and friendship. This study aims to examine how morality is depicted in the play using Friedrich Nietzsche's theory of ‘master morality’ and ‘slave morality’. This study uses a descriptive qualitative method by analysing excerpts from the dialogue in the play “Timon of Athens” that demonstrate moral values. The results show that this play mostly depicts slave morality (65%), as Timon transforms from a kind and proud figure into someone filled with hatred and resentment after being betrayed. Meanwhile, master morality (35%) appears at the beginning of the story when he is still strong, confident, and generous. According to Nietzsche, master morality reflects strength, pride, independence, and the ability to create one’s own values, while slave morality emerges from weakness, suffering, and resentment as a reaction to disappointment or oppression. Overall, Timon of Athens illustrates how life changes and deep betrayal can cause a shift from the confidence and generosity of master morality to the bitterness and hatred found in slave morality.